Observation of Clinicopathologic Features of Pituitary Adenoma With Neuronal Differentiation - Zheng, Limei; Yan, Xiaorong; Hu, Chengcong; Zhang, Peng; Chen, Yupeng; Zheng, Qiaoyan; Hu, Liwen; Wang, Mi; Li, Guoping; Wu, Ping; Jiang, Changzhen; Tian, Jing; et al. (Frontiers in Endocrinology, 2022)
Objective To investigate the clinicopathologic features of pituitary adenoma with neuronal differentiation. Methods Four patients with mixed gangliocytoma-pituitary adenomas between January 2011 and January 2021 and 111 new-onset patients with adenomas between January 2019 and June 2021 who attended the First Affiliated Hospital of Fujian Medical University were included in the study. The histological and immunohistochemical findings were analyzed. Neuronal differentiation marker staining was performed on new-onset adenomas, and the related literature was reviewed. Results Altogether, more than 100 mixed gangliocytoma-pituitary adenoma cases have been reported in the literature until now, of which pituitary-specific POU-class homeodomain transcription 1 (PIT1) positive adenomas are more frequently observed. In the present study, all 4 patients we described were female, aged 29 to 53 years (mean 39 years). Clinically, 3/4 patients presented with acromegaly, and 1/2 patients presented with headache. Histologically, the tumor was composed of two distinct mixed components. The one was a population of neoplastic ganglionic cells with large nuclei, prominent nucleoli, and abundant basophilic cytoplasm embedded in a fibrillary background. Stains of chromograninA (CgA), synaptophysin (Syn), Calretinin (CR) were positive. Axotomy-like expression was observed in neurofilament (NF) staining. PIT1 was expressed in partial ganglionic cells in all cases. The other component was a population of small uniform cells with round nuclei and acidophilic cytoplasm. Prolactin (PRL) and growth hormone (GH) were positive in all 4 cases. PIT1 was positive in the nuclei of adenomas. Although adenomas and ganglionic regions varied in histology, there was a population of cells with neuronal differentiation expressing PIT1. Additionally, axotomy-like expression of NF staining could be seen in a distant area of adenoma regions. A total of 111 cases of adenomas without ganglionic cells were included in this study, including 7 cases with neuronal differentiation. Among them, 4 cases were prolactinomas, 2 cases were somatotroph adenomas, and 1 case was corticotroph adenoma. 6/7 cases were PIT1-positive adenomas. And the remaining one case is T-PIT-positive adenoma. Conclusions Mixed gangliocytoma-pituitary adenomas are rare tumors with neuronal differentiation. The majority of MGAs are associated with endocrinopathies, mainly acromegaly. Our results suggest that PIT1-positive pituitary adenomas may have neural differentiation potential, which may not be unusual. This indication supports the possibility that the neuronal transdifferentiation of adenomatous cells is a possible mechanism, and the underlying mechanism requires further elucidation.